2015
DOI: 10.3791/52302
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Cognition Using Transcranial Direct Current Stimulation of the Cerebellum

Abstract: Numerous studies have emerged recently that demonstrate the possibility of modulating, and in some cases enhancing, cognitive processes by exciting brain regions involved in working memory and attention using transcranial electrical brain stimulation. Some researchers now believe the cerebellum supports cognition, possibly via a remote neuromodulatory effect on the prefrontal cortex. This paper describes a procedure for investigating a role for the cerebellum in cognition using transcranial direct current stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The sequences used in each task before and after the stimulation period were different, and the numbers in the sequences were in the range of 1–9. Details of each task can be found elsewhere ( Pope 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sequences used in each task before and after the stimulation period were different, and the numbers in the sequences were in the range of 1–9. Details of each task can be found elsewhere ( Pope 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the more consistent processes associated with cerebellar activation involves tasks related to working memory or executive function. 31,61-66 Cerebellar activation has also been identified with tasks of attention and timing. 67-70 As with the cerebellar role in language, studies on a cerebellar contribution to cognition largely support a role for the lateral cerebellar hemispheres in supporting cognitive processes.…”
Section: Cognitionmentioning
confidence: 99%
“…Other studies investigating the cognitive effects of cerebellar stimulation using tDCS have similarly produced mixed findings. Pope , for example, recently showed that cathodal, but not anodal, tDCS applied to the right cerebellum improved performance on a difficult working memory task. In another study, however, cathodal tDCS similarly given to the right cerebellum reduced practice effects on an auditory attention and working memory task .…”
Section: Discussionmentioning
confidence: 99%